2011
DOI: 10.1007/s12253-010-9355-6
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Carbonic Anhydrase IX (CA-IX), Endoglin (CD105) and 8-hydroxy-2′-deoxyguanosine (8-OHdG) in Breast Cancer Patients

Abstract: The aim of this study was to examine the prognostic significance of carbonic anhydrase IX (CA-IX), an endogenous marker for tumor hypoxia; endoglin (CD105), a proliferation-associated and hypoxia-inducible glycoprotein and 8-hydroxy-2'-deoxyguanosine (8-OHdG), an oxidative DNA lesion, in breast cancer patients. Immunohistochemical expressions of CA-IX, CD105 and 8-OHdG, analyzed on paraffin-embedded tumor tissues from forty female breast cancer patients, were used to assess their prognostic implication on over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…In breast cancer, abundant expression of CAIX and GLUT‐1 is associated with high‐grade cancers . CAIX has been linked to shorter relapse‐free survival in patients with grade I and II tumours and to poor prognosis in invasive breast carcinoma . CAIX has also been suggested as a predictive marker for response to chemotherapy and adjuvant treatment in patients with breast cancer .…”
Section: Hypoxia‐inducible Factorsmentioning
confidence: 99%
“…In breast cancer, abundant expression of CAIX and GLUT‐1 is associated with high‐grade cancers . CAIX has been linked to shorter relapse‐free survival in patients with grade I and II tumours and to poor prognosis in invasive breast carcinoma . CAIX has also been suggested as a predictive marker for response to chemotherapy and adjuvant treatment in patients with breast cancer .…”
Section: Hypoxia‐inducible Factorsmentioning
confidence: 99%
“…In our previous study we have shown that high expression of CAIX was a strong independent prognostic indicator for shorter OS and recurrence-free survival (RFS) for patients with invasive ductal breast carcinoma (18). The objective of this study was to examine the expression of the hypoxic marker CAIX relative to expressions of the apoptosis regulator Bcl-2, tumor suppressor protein p53 and proliferative index Ki-67, to examine the role of hypoxia in TNBC.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, CAIX expression in cancers can be induced by the hypomethylation of the CA9 promoter or by inactivating mutations in the VHL gene that may drive the overexpression of CAIX independently of hypoxic conditions [12][13][14]. Most of the studies show that its overexpression in BC is a poor prognostic marker for distant metastasis and survival [15][16][17]; however, several other studies did not find a significant association with relapse-free or overall survival [18,19]. It seems likely that these contradictory findings at least partially may be explained by its differential expression in various subtypes of BC [16,20]; however, the prognostic significance of CAIX expression within the subtypes has not been systematically studied so far.…”
Section: Introductionmentioning
confidence: 99%